PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI DENGAN MENGGUNAKAN DIMENSI FRAUD DIAMOND - Endang Masitoh W., Dyah Noviana Primasari, Suhendro & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
This research examined factors that influence the behavior of student’scheating by using the concept of fraud diamond consisting of pressure,opportunity, rationalization, and individual’s capability. This researchpopulation is students S1 college in Surakarta that was active. Sample used inthis research is students department of economics S1 accounting courses collegein Surakarta. Sample selection using purposive sampling method. In this researchuse research instruments a questionnaire. The research sample obtained by 129students department of economics S1 accountinng courses college in Surakarta.Methods of data analysis using multiple linear regression analysis. The result ofthis research show that opportunity and capability individual’s have positivesignificant effect to students academic fraud behavior committed by accountingstudents, whereas pressure and individual’s capability did not influence tostudents academic fraud behavior committed by accounting students.Keywords: academic fraud, fraud diamond, accounting students, college,Surakarta.